Disaster Mitigation Based on Regional Vulnerability Analysis of South Labuhanbatu Regency for Risk Reduction Planning - Ulil Amri Daulay; Agus Purwoko; Prawidya Hariani RS; Ridwan; Rizky Wahyudi; Iskandar; Rizky Adrian (TERRA: Journal of Forest Management, 2026)
Disaster mitigation is a systematic effort to reduce disaster risks through pre-disaster planning, vulnerability reduction, and capacity building to support sustainable development. In South Labuhanbatu Regency, geographic conditions, climate change, and land-use dynamics, particularly lowlands, dense river networks, high rainfall, and extensive oil palm plantations, increase the risk of flooding and environmental degradation. Therefore, mitigation efforts must be specific, based on a vulnerability analysis that integrates environmental aspects into spatial planning strategies. Data analysis was conducted spatially using GIS through map digitization and georeferencing, land use classification, and overlay analysis between physical conditions of the region, land use, and disaster potential. Spatial analysis shows that is dominated by flood hazards, covering 34,224.8 Ha (9.59%) of the total area, mainly in Kampung Rakyat, Kotapinang, Sungai Kanan, and Torgamba, while Silangkitang is not flood-prone. Flood vulnerability is closely related to lowland areas along the Barumun Watershed, where peatland conditions and oil palm–dominated land use reduce infiltration and increase surface runoff. Landslide hazards are limited to Torgamba and Sungai Kanan due to hilly terrain and land clearing, while active fault intensity varies spatially, with the highest levels in Silangkitang, highlighting the importance of integrating geological risk into spatial planning.